Redrawing the Panorama of Interpreting Theory: A Review on “Theorising Interpreting Studies” - Gao, Wang-qi (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Theorising Interpreting Studies addresses the long-standing fragmentation and lack of systematic theoretical frameworks in Chinese interpreting research by constructing a multi-dimensional epistemology that integrates micro-level cognitive processing, meso-level communicative coordination, and macro-level socio-cultural perspectives. Wang Binhua proposes seven theoretical modules, encompassing interpreting as a bilingual conversion process, a cognitive operation, an information-processing mechanism, a discourse comprehension and production activity, interpersonal and cross-cultural communication behavior, and professional competence. The book develops multi-level and multimodal research pathways, connecting empirical investigation with theoretical analysis, and provides structured frameworks for community interpreting, interpreter roles, ethical norms, historical research, and interdisciplinary development. A distinctive feature of the work is its critical engagement with classical Western theories, including the Paris School’s Interpretive Theory and cognitive load models, while simultaneously integrating Chinese-specific practices, such as dialect and minority-language interpreting, thereby achieving a localized yet globally informed theoretical synthesis. The book emphasizes interpreting as a complex cognitive–informational–social activity and demonstrates methodological rigor through the combination of literature review, conceptual analysis, and empirical modeling. Key contributions include overcoming theoretical fragmentation, fostering cross-cultural academic dialogue, and offering practical guidance for scholars and graduate students. While minor gaps remain in aligning micro-level theoretical modules and balancing descriptive exposition with critical evaluation, the work provides a comprehensive reference for the advancement of interpreting theory, clarifies developmental trajectories, and suggests research pathways for future interdisciplinary exploration, cross-cultural dialogue, and the integration of local practices into global scholarly discourse. This book thus represents a milestone in consolidating empirical and theoretical research in interpreting studies and offers a systematic foundation for the continued development of the discipline.